Geographical distribution of rural settlements in the center of the eastern district of Hamza and Al-Shinafiyah district - وهاب فهد الياسري; مجيد حميد البدري; هاتف لفته الجبوري (آداب الكوفة, 2016)
The research aims to reveal the pictures of the geographical distribution of the rural settlements in the study area, as it was divided into the volumetric distribution and the density distribution of the settlements, as well as to reveal the patterns of the geographical distribution of the rural settlements, the extent of their concentration or spread, and to know the extent of the influence of geographical factors (natural and human). To achieve this, quantitative methods were used, namely Logarithmic transformation technique in the classification of size and density classes and the nearest neighbor connotation to detect distribution patterns in order to develop development plans and develop rural settlements. The GIS technique was used to measure distances based on satellite images of the study area as well as in mapping.